PSYCHOLOGICAL RESILIENCE AND ITS RELATIONSHIP TO SOCCER SCORING ACCURACY - Ibrahim, Ammar Mousa (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The preparing the players well from the psychological point of view in addition to the physical will make the player able to face the various challenges and different circumstances of the player and achieve the highest sports levels, and here is the value of article. in studying the relationship between psychological flexibility and scoring accuracy in soccer. As for the research objectives Identify the psychological resilience of soccer players and identifying the relationship between psychological resilience and soccer scoring accuracy. The research community is represented by the players of the University of Babylon soccer team, who are (25) players. (20) players were selected from the research community to represent the research sample, as homogenization was carried out for the sample members according to the research controls. After conducting the tests concerned with the research, the data was collected and processed statistically, and then the results were extracted on the basis of which the conclusions were built, the most important of which is there was no clear relationship between psychological resilience and accuracy in the current study, as the research sample was represented by the soccer team at the university, which is considered an advanced category.